Oral health care in older people in long-term care facilities: An updated systematic review and meta-analyses of implementation strategies - Lina F. Weening-Verbree; Anouk Douma; Cees P. van der Schans; Getty J. Huisman-de Waal; Annemarie A. Schuller; Sytse U. Zuidema; Wim P. Krijnen; Johannes S.M. Hobbelen (International Journal of Nursing Studies Advances)
Introduction: Oral health care of older people in long-term care facilities is insufficient, stressing the need for clear evidence-based implementation strategies to improve oral care. In 2013, a systematic review was performed and new evidence was published. This study aimed to gain insights into implementation strategies used to promote or improve oral health care for older people in long-term care facilities, explore their effectiveness and uncover strategy content in behavioral change techniques, and report the differences between the current results and those of the 2013 study. Methods: A systematic review of the literature according to PRISMA guidelines and meta-analyses of implementation strategies were performed. Cochrane Library, PubMed, and CINAHL databases were searched for papers published between 2011 and 2023. Strategies were identified using the Coding Manual for Behavioral Change Techniques. Meta-analyses of oral health outcomes (“plaque” and “denture plaque”) were performed with random-effects models using R language for statistical computing. Results: 16 studies were included in the current results; 20 studies were included in the 2013 findings. More high-quality studies (67 %) were included in this review than in 2013 (47 %). Dental care professionals were involved in 14 of the 16 studies. Fourteen of the 16 studies used and/ or combined five or more different implementation strategies: knowledge, intention, awareness, self-efficacy, attitude, and facilitation of behavior. Implementation positively affected the knowledge and attitudes of the nursing staff; however, the oral health of older people did not necessarily improve. In the 2013 review, more studies indicated combined oral health measurements were effective (71 %) than in the current review (20 %–33 %). Meta-analysis of four studies on dental plaque (0—3 scale) showed a significant, statistically small mean difference of -.21 (CI -.36; -.07, Cohen's d -.29) between the control and treatment group. Meta-analysis of three studies on denture plaque (0—4 scale), showed a significant, statistically large mean difference of -.76 (CI -1.48; -.05, Cohen's d -.88). Conclusions: In this review, more implementation strategies and combinations were used to implement oral care in long-term care. Implementation strategies positively affected the knowledge and attitudes of nursing staff; however, the oral health of older people did not necessarily improve. Meta-analyses on plaque showed that oral care implementations are effective; for denture plaque, the effect size was large and thus may have more clinical value than for dental plaque.